1967
DOI: 10.3758/bf03331152
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the electroencephalogram, eye-movements and fluctuations of visual perception

Abstract: Relationship between the electroencephalogram, eye-movements and fluctuations of visual perceptionEEG activity and eye movements were recorded while 5s inspected a Ganzfeld or diffuse dark figures introduced into a Ganzfeld. Reports of deterioration of visual perception under all stimulus conditions were preceded by a period of reduced eye movement, but were not associated with a return of EEG alpha activity.Observers report an experience of blank-out or loss of visual perception after a period of exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

1968
1968
1997
1997

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…These results are in-many respects similar to data obtained from experiments with stabilized retinal images, as might be expected from the evidence that the reports of fading of images under conditions similar to those used in this experiment are invariably associated with periods of reduced eye movement (Kirkwood, 1967). Riggs et al (1953) reported that images of fine lines fade more rapidly than those of thick bars when stabilized on the retina.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results are in-many respects similar to data obtained from experiments with stabilized retinal images, as might be expected from the evidence that the reports of fading of images under conditions similar to those used in this experiment are invariably associated with periods of reduced eye movement (Kirkwood, 1967). Riggs et al (1953) reported that images of fine lines fade more rapidly than those of thick bars when stabilized on the retina.…”
Section: Discussionsupporting
confidence: 88%
“…Even areas of inhomogeneous hue or brightness introduced into an otherwise uniform field are perceptually unstable and seem to fade into their background after a time (Guilford, 1927;Cohen, 1958;Kirkwood 1967). These effects appear consistent with findings from work with stabilized retinal images.…”
supporting
confidence: 83%
See 1 more Smart Citation